H08 Neuropsychiatric Burden In Huntington Disease. (17th September 2014) - Caletti, E; Botturi, A; Zugno, E; Prunas, C; Cigliobianco, M; Paoli, RA
Abstract : Background: The clinical manifestations of Huntington Disease include motor, cognitive and psychiatric disturbances. There is a wide spectrum of symptoms and the presence of disorders in psychiatric field worsens autonomy and quality of life of the patients. Main psychiatric syndromes may appear during progression of Huntington Disease, often in a non-typical way. Some authors have noticed even 20 years before onset of chorea or dementia symptoms of Huntington Disease. Aims: We present a review of literature describing the main psychopathological pictures in Huntington Disease, whose prevalence is estimated between 33% and 76%. Results: It is possible to make diagnosis of major depression in a percentage between 9% and 63%, and the suicide rate in patients is 4 to 6 times higher than normal population, with greater prevalence among patients over 50 years old. Hypomania and mania have been estimated in 4, 8% to 10% of patients. Anxiety has been less studied however some studies report that it also occurs frequently (34–61%). Prevalence of irritability varies between 38% and 73%, whereas obsessive and compulsive symptoms are comprised between 5% and 52%. A picture of psychosis has prevalence estimated at 4% to 12%. Delirium, apathy and neuropsychological impairments are strictly correlated with the progression of the disease. Conclusions: It is important to recognise psychiatric facets in HD, in order to tailor the psychopharmacological therapy and reduce the burden for the caregiver.